2016
DOI: 10.1103/physrevlett.116.054501
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Generation of Vorticity by Surface Waves

Abstract: We demonstrate that waves excited on a fluid surface produce local surface rotation owing to hydrodynamic nonlinearity. We examine theoretically the effect and obtain an explicit formula for the vertical vorticity in terms of the surface elevation. Our theoretical predictions are confirmed by measurements of surface motion in a cell with water where surface waves are excited by vertical and harmonic shaking the cell. The experimental data are in good agreement with the theoretical predictions. We discuss physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 8 publications
3
27
1
Order By: Relevance
“…2. The result is in agreement with earlier measurements [5,17], see also the discussion of these papers in Ref.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…2. The result is in agreement with earlier measurements [5,17], see also the discussion of these papers in Ref.…”
Section: Discussionsupporting
confidence: 94%
“…VI.A]. We have calculated both these quantities (4) and (5) and found that the obtained value of the film compression modulus ε leads to the values which are in a reasonable agreement with the experimental data, see Fig. 5.…”
Section: Discussionsupporting
confidence: 77%
“…This results in a small displacement of the particle in the direction of the wave propagation when a wave cycle is completed. Note that the physics of the Lagrangian circular drift revealed here is intrinsically different from a recent Eulerian theory of vorticity generation on a surface perturbed by waves, which considers bulk viscosity as the essential ingredient of the mechanism 22 .…”
Section: Resultscontrasting
confidence: 58%
“…58 Several nonlinear models based on potential or viscous flows near a free surface have been proposed. 52,55,[59][60][61] An interesting path could be related to the Stokes drift induced by the variation of the temporal phase of 2D quasi-standing waves as shown in Fig. 9(b).…”
Section: D Turbulence In Faraday Wavesmentioning
confidence: 99%